Saving the sun dragon ebook - West, Tracey (Dragon Masters, 2015)
DRAGON MASTERS has it all—dragons, Dragon Stones, a wizard, and even some magic! This series is part of Scholastic's early chapter book line called Branches, which is aimed at newly independent readers. With easy-to-read text, high-interest content, fast-paced plots, and illustrations on every page, these books will boost reading confidence and stamina. Branches books help readers grow! In the second book in this fully-illustrated series, Drake and the other three Dragon Masters (Ana, Rori, and Bo) continue their training. But Ana's dragon, Kepri, is sick. The wizard tries to make her feel better, but his potions are not working. Drake's dragon, Worm, must use his special powers to take the Dragon Masters across the world in search of a cure. What made Kepri sick? Will the Dragon Masters be able to save her? And what dangers will they face along the way?